A reflection on the constitution of drag queens in dialogue with the personifications of Japan (ModaPalavra e-periódico, 2025)
Drag Queens are a reference in the history of theater and perfor-mance, in gender discussions and in fashion research. In the West, this mark of diversity emerges more strongly in the media, from the 1990s onwards in the United States. In Asia, it can be said that there is a dialogue between Drag and the Arts of the Body, which dates back to the seventeenth century, and clothes and makeup ended up acting as body activators, thus surpassing the traditional notion of costume. This article aims to discuss the performative constitution of Drag Queens specifically documented by Cláudia Guimarães in São Paulo and of onnagata actors from kabuki theater in interface with some characters from Kazuo Ohno’s butoh dance. The methodology involves bibliographic research supported mainly by the bodymedia theory (Katz; Greiner, 2015) and iconograph-ic research to qualitatively analyze singularities of bodies outside heteronormative standards, pointing out how trans fashion has ac-tivated political and existential issues that have already completed four centuries and can be considered a fabulatory device to make subjectivities explicit.
Keywords: drag queen; onnagata; fabulation